Effects of distillers grains on growth performance in nursery and finishing pigs - Senne, B.W.; Sorrell, P.S.; Kim, I.H.; Traylor, S.L.; Hines, Robert H.; Hancock, Joe D.; Behnke, Keith C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Rate and efficiency of gain were not affected by adding as much as 20% distillers dried grains in isocaloric diets for nursery pigs or 30% in isocaloric diets for finishing pigs. These results demonstrate that the previously suggested maximums of 5% distillers dried grains in nursery diets and 10% distillers dried grains in finishing diets are too conservative. Finally, because the 20% (nursery) and 30% (finishing) treatments were the greatest concentrations used in our experiments, additional growth assays are needed to determine the maximum limits for distillers dried grains in diets for pigs.
Keywords: Swine; Distillers grains; Nursery; Finishing; Sorghum